Іслам крізь призму українських мас-медіа: основні напрями сучасних наукових досліджень - Козиряцька, Світлана Анатоліївна; Козыряцкая, С. А.; Kozyryatska, S. (Класичний приватний університет, 2018)
У статті проаналізовано праці українських науковців, які вивчали проблеми релігійної журналістики з погляду висвітлення ісламської (мусульманської) тематики в українських ЗМІ, та в хронологічному вимірі визначено коло актуальних питань, що становили науковий інтерес дослідників. Виокремлено проблеми, пов’язані з формуванням образу мусульман та ісламської або національної ідентичності українськими медіа в умовах різновекторності інформаційного впливу (з боку Росії та країн Західної Європи), а також дуальності російського вектора впливу. Відзначено ситуативність і бінарність у висвітленні етнорелігійних питань українськими ЗМІ, що зумовлені як геополітичною ситуацією в Україні та світі, так і впливом зовнішнього медійного поля, а також рівнем компетентності журналістів у питаннях релігії. В статье проанализированы труды украинских ученых, которые изучали проблемы религиозной журналистики с точки зрения освещения исламской (мусульманской) тематики в украинских СМИ, и в хронологическом измерении определен круг актуальных вопросов, которые составляли научный интерес исследователей. Выделены проблемы, связанные с формированием образа мусульман и исламской или национальной идентичности украинскими медиа в условиях разновекторности информационного воздействия (со стороны России и стран Западной Европы), а также дуальности российского вектора влияния. Отмечено ситуативность и бинарность в освещении этнорелигиозных вопросов украинскими СМИ, обусловленные как геополитической ситуацией в Украине и мире, так и влиянием внешнего медийного поля, а также уровнем компетентности журналистов в вопросах религии. Research methodology. The research ground is the information approach; the method of scientific literature analysis was used for the general exploration of the subject, for the detection of level of theoretical study of such aspect of religious journalism, as Islamic (Muslim) topics; the generalization method was used to determine in chronological dimension the topical issues of religious journalism in the context of Islamic (Muslim) topic coverage. Results. The article analyzes the papers of Ukrainian scholars engaged in studying of religious journalism problems in regard to the Islamic (Muslim) topic coverage in Ukrainian mass media and in chronological dimension defines the spectrum of topical issues relevant for researchers’ academic interest. The article highlights problems related to the shaping of image of Muslims and Islamic or national identity by Ukrainian media in the context of different vectors of information influence (from Russia and Western Europe countries) and duality of Russian influence vector. The article notes the situationalness and binarity in the coverage of ethnic and religious questions by Ukrainian mass media, determined not only by geopolitical situation in Ukraine and the world, but also by external media field influence, as well as by a level of journalist competence in religious questions. Novelty. The novelty of the article consists in the systematization of academic achievements of Ukrainian scholars in the field of religious journalism in the context of Islamic (Muslim) topics coverage in Ukrainian mass media and the determination in chronological dimension the number of topical issues relevant for their academic interest. The article defines a spectrum of promising trends of academic research in this sphere, determined by geopolitical situation in Ukraine and the world, and also by external media field influence (from Russia and Western Europe countries).
Ислам сквозь призму украинских масс-медиа: основные направления современных научных исследований
Islam in the Light of Ukrainian Mass Media: the Main Directions of Modern Academic Researches
Keywords: українські медіа; стереотипізація ісламу; етнорелігійні стереотипи; образ мусульман у ЗМІ; наклеювання ярликів; вектор інформаційного впливу; украинские медиа; стереотипизация ислама; этнорелигиозные стереотипы; образ мусульман в СМИ; наклеивание ярлыков; вектор информационного воздействия; ukrainian media; stereotyping of Islam; ethno-religious stereotypes; Muslims image in mass media; labelling; information influence vector